2007
DOI: 10.1002/anie.200605254
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Charge‐Reversal Nanoparticles for Nuclear Drug Delivery

Abstract: Reversing the charges: Targeted charge‐reversal nanoparticles (TCRNs) comprised of poly(ε‐caprolactone)‐block‐polyethyleneimine (PCL‐PEI), whose amine groups are converted into amides, are negatively charged at neutral pH but become positively charged at pH<6 (see picture). TCRNs effectively enter cells, regenerate the PEI layer in lysosomes, and localize in the nucleus for nuclear drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
289
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 359 publications
(302 citation statements)
references
References 31 publications
6
289
0
7
Order By: Relevance
“…Free DOX enters cancer cells and preferentially labels their nuclei in 3 h as we have previously reported ( Figure 4 ). [ 11 ] We also noticed that in the confocal signature of the nanogel disappeared with the size increase. We think the loss of the multicompartment pattern was due to the break of disulfi de bonds and the subsequent reorganization of the nanogel.…”
Section: Communicationmentioning
confidence: 86%
“…Free DOX enters cancer cells and preferentially labels their nuclei in 3 h as we have previously reported ( Figure 4 ). [ 11 ] We also noticed that in the confocal signature of the nanogel disappeared with the size increase. We think the loss of the multicompartment pattern was due to the break of disulfi de bonds and the subsequent reorganization of the nanogel.…”
Section: Communicationmentioning
confidence: 86%
“…A similar pH influence on zeta potential has been reported previously in the literature. [25][26][27] As a result, the use of LPH nanoparticles may dramatically enhance the concentration of the drug in cells, thereby improving drug cytotoxicity and more effectively overcoming MDR in cancer cells (Figure 4). In all cell lines studied, DTX exhibited a time-and dose-dependent cytotoxic effect.…”
Section: In Vitro Cell Studiesmentioning
confidence: 99%
“…Vast majority of the laser Ag NPs is located outside the A594 cell membrane ( Figure 8A). Previous finding by Xu et al 42 demonstrated that NPs located in the nuclei or ribosomes of the cells were more toxic than those in the cytoplasm, even at low concentrations. In our study, we did not observe any laser Ag-TiO 2 NPs that were in the nuclei.…”
mentioning
confidence: 93%